Validation of the portuguese version of the healthy life styles questionnaire - Batista, Marco (2019)
The aim of this study was the adaptation and validation the Portuguese version of Healthy Lifestyle Questionnaire, adapted of Wold (1995), using an exploratory and confirmatory factor analysis of the measurement model, with a sample of sports veterans. It was a) conducted a reverse translation; b) translated again by a translator unrelated to the research group to English, where he noted a great similarity with the original questionnaire also after retroversion process; c) evaluated by three experts in the field; d) administered the questionnaire to a small group of athletes with similar ages to the final sample to verify its correct understanding, not noticing any problems of reading comprehension; e) quiz application for approximate time of completion was about, fifteen minutes; f) data processing. The internal consistency of each factors resulting from the factor analysis (Cronbach's alpha) showed the following results: (.80) eating habits (.91) tobacco consumption, (.84) resting habits. The reliability coefficient should be above the .70. There were also values of 0.861 on the KMO and Bartlett's test, where 56.24% of the variance is explained by three factors. After analysis, it was shown that the 20 items were grouped into three factors, respectively: eating habits (10 items), tobacco consumption (5 items) and resting habits (5 items). In a similar way, the standardized factor loads were all statistically significant (p <.01). The preliminary analysis of the data also indicated that the sample did not meet the criterion of normality, since the Mardia coefficient was high (62.43). For that reason, we used the robust estimation method of verisimilitude maximum. After a first analysis, the overall model results indicated a reasonable adjustment of the Healthy Lifestyles Questionnaire: (χ2 = 172,117, p = .000, χ2 / df = 4.190, CFI = .966, IFI = .966, MFI = .909, GFI = .955, AGFI = .927, RMA = .049, RMSEA = .068, SRMR = .043). Thus, we can conclude that the adaptation to Sports of the Portuguese version of the Healthy Lifestyles Questionnaire, can be used with confidence of validity and reliability in the evaluation of healthy lifestyles, underlying to the self-determination theory in sport context.